Question & Answer: Consider the following function. (a) What would be the response to the call fun with no arguments? (b) Rewrite it (the function an…..

7. (10 points) Consider the following function. (a) What would be the response to the call fun with no arguments? (b) Rewrite it (the function and default x) so that it evaluates post fix notation expres- sions that are formed as nested cell arrays. function [t]- fun (x) if nargin-= 0 x- 15 692518 6: end if iscel1(x) switch x(1) case + case - case t = fun (x(2)) + fun (x(3)); t fun (xf2)) fun (x(3)); t = fun(x(2)) * fun (x(3)); t = fun (x(2)) / fun (x(3)); case , end else t = x; end

Consider the following function. (a) What would be the response to the call fun with no arguments? (b) Rewrite it (the function and default x) so that it evaluates post fix notation expressions that are formed as nested cell arrays. function [t] = fun(x) if nargin == 0 x = { ‘+’ { ‘-‘ { ‘*’ 9 2 } 5} { ‘/’ 18 6 } } }: end if iscell(x) switch x(1) case ‘+’ t = fun (x{2}) + fun (x{3}): case ‘-‘ t = fun (x{2}) – fun (x{3}): case ‘*’ t = fun(x{2}) * fun (x{3}): case ‘/’ t = fun (x{2})/fun (x{3}): end else t = x: end

Expert Answer

 

[a]

Code :

function [t] = fun(x)

if nargin ==0

x = {‘+’ {‘-‘ 15 6} {‘-‘ {‘-‘ {‘*’ 9 2} 5 } {‘/’ 18 6}}};

end

if iscell(x)

switch x{1}

case ‘+’

t= fun(x{2}) + fun(x{3});

case ‘-‘

t = fun(x{2}) – fun(x{3});

case ‘*’

t = fun(x{2}) * fun(x{3});

case ‘/’

t = fun(x{2}) / fun(x{3});

end

else

t =x;

end

Result :

Question & Answer: Consider the following function. (a) What would be the response to the call fun with no arguments? (b) Rewrite it (the function an..... 1

Still stressed from student homework?
Get quality assistance from academic writers!